2010
DOI: 10.1007/s10709-010-9479-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel female-specific splice form of dsx in the silkworm, Bombyx mori

Abstract: The Bombyx mori doublesex (Bmdsx), a homologue of doublesex of Drosophila, is the bottom most gene of the sex determination cascade. Bmdsx plays a very crucial role in somatic sexual development. Its pre-mRNA sex-specifically splices to generate two splice variants; one encodes female-specific and the other encodes male-specific polypeptides which differ only at their C-termini. The open reading frame of Bmdsx consists of 5 exons, of which exons 3 and 4 are female-specific and are skipped in males. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 47 publications
3
28
0
Order By: Relevance
“…Two relevant splice variants are indicated. Additional splice variants are known for both Bmdsx and Pgdsx (13,35,36). E, exons; I, introns.…”
Section: Resultsmentioning
confidence: 99%
“…Two relevant splice variants are indicated. Additional splice variants are known for both Bmdsx and Pgdsx (13,35,36). E, exons; I, introns.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies reported that Bmdsx transcripts are spliced in a sex-specific manner to yield two female forms ( Bmdsx F1 and Bmdsx F2 ) and one male form ( Bmdsx M ) [19,30]. In a recent study, we predicted the existence of a novel exon, 2n, and a third female-specific splice form Bmdsx F3 [31].…”
Section: Resultsmentioning
confidence: 94%
“…This is the case in M. domestica and A. mellifera in which in addition to sex-specific transcripts there is a dsx transcript encoding a common Dsx protein in males and females [26,27]. In Aedes aegypti , A. assama , A. mylitta and B. mori a second female-specific Dsx protein is predicted [28-30]. Recently, we proposed that B. mori has a third female-specific Dsx protein predicted to arise from a novel trans-spliced transcript, Bmdsx-dsr2 d [31].…”
Section: Introductionmentioning
confidence: 99%
“…A dsx homolog (Bmdsx) in B. mori is present on chromosome 25, and its pre-mRNA is spliced in a sex-specific manner producing 2 female-and 1 male-specific isoforms Shukla et al, 2011]. Bmdsx harbors 5 exons and 4 introns out of which exons 1, 2, and 5 are constitutively spliced, whereas exons 3 and 4 are female-specific .…”
Section: Dsx Homologs In Lepidopteransmentioning
confidence: 99%
“…Bmdsx harbors 5 exons and 4 introns out of which exons 1, 2, and 5 are constitutively spliced, whereas exons 3 and 4 are female-specific . Both female-specific isoforms of Bmdsx differ from each other by a 15-bp alternatively spliced (alternative 5 ′ splice site selection) sequence present after exon 3 [Shukla et al, 2011]. Due to this difference, both BmDSX F proteins differ from each other by 18 amino acids.…”
Section: Dsx Homologs In Lepidopteransmentioning
confidence: 99%